A comparison of geomembrane wrinkles for nine field cases. Issue 6 (1st December 2012) - Take, W.A.; Chappel, M.J.; Brachman, R.W.I.; Rowe, R.K.
Abstract : ABSTRACT: The length of the longest wrinkles formed in black, exposed high-density polyethylene (HDPE) geomembranes are compared for nine different field cases for a range of different conditions (base or slope; GCL, CCL (geosynthetic clay liner) or sand subgrade below geomembrane; geomembrane thicknesses of 1.5 mm and 2 mm, and textured or smooth geomembrane). The size of the geomembrane area that was restrained was shown to limit the longest connected wrinkle that developed. Of the cases examined, the longest wrinkle was 5330 m for a 1.5 mm-thick geomembrane on sand on a 0.61 ha west-facing 3H:1V side slope. On the smallest geomembrane areas (less than 0.09 ha in this study), the longest observed connected wrinkles throughout the day were less than 550 m. The average wrinkle widths were 0.20–0.23 m and 0.24–0.32 m resting on a GCL and CCL, respectively. Wrinkle height was found to average 0.06 m and the maximum height was 0.18 m. When less than 8% of the geomembrane was wrinkled and the sum of the wrinkle lengths was less than 600 m, the longest connected wrinkle was less than 200 m. Data from these nine cases show that, on sunny days, restricting covering of the geomembrane to the early morning or late afternoon and/or reducing the restrained area of geomembrane to 0.05 ha (or less) will minimise the risk of the formation of long connected wrinkles for environments similar to those examined.